Prevotella timonensis degrades the vaginal epithelial glycocalyx through high fucosidase and sialidase activities - Perez, Celia Segui; Jongh, Rivka De; Jonkergouw, Robin; Pelayo, Paula; Balskus, Emily P.; Zomer, Aldert; Strijbis, Karin (bioRxiv, 2024)
Bacterial vaginosis (BV) is a polymicrobial infection of the female reproductive tract (FRT). BV is characterized by replacement of health-associated Lactobacillus species by diverse anaerobic bacteria, including the well-known Gardnerella vaginalis. Prevotella timonensis and Prevotella bivia are anaerobes that are found in a significant percentage of BV patients, but their pathogenic properties are yet to be determined. Defining characteristics of anaerobic overgrowth in BV are adherence to the mucosal surface and the increased activity of mucin-degrading enzymes such as sialidases in vaginal secretions. Here, we demonstrate that P. timonensis but not P. bivia strongly adhered to vaginal and endocervical cells to a similar level as G. vaginalis but did not elicit a comparable pro-inflammatory response. The P. timonensis genome uniquely encodes a large set of mucus-degrading enzymes including 4 putative fucosidases and 2 putative sialidases, PtNanH1 and PtNanH2. Enzyme assays demonstrated that fucosidase and sialidase activity in P. timonensis cell-bound and secreted fractions was significantly higher than for other vaginal anaerobes. Infection assays revealed that P. timonensis fucosidases and sialidases efficiently removed fucose and α2,3- and α2,6-linked sialic acid moieties from the epithelial glycocalyx. Recombinantly expressed P. timonensis NanH1 and NanH2 efficiently removed α2,3 and α2,6-linked sialic acids from the epithelial surface and sialic acid removal by P. timonensis could be blocked using inhibitors. This study demonstrates that P. timonensis has distinct virulence properties that include initial adhesion and a high capacity for mucin degradation at the vaginal epithelial mucosal surface. Our results underline the importance of understanding the role of different anaerobic bacteria in BV.